Pediatric Pneumococcal Serotypes in 4 European Countries - Hanquet, Germaine (Centers for Disease Control and Prevention, 2010)
After heptavalent pneumococcal conjugate vaccine (PCV7) was marketed in France, Spain, Belgium, and England and Wales (United Kingdom), invasive disease from non-PCV7 serotypes (NVT) increased. Adjusted serotype-specific incidences among children <15 years of age were compared between 1999–2002 (prevaccine) and 2005–2006 (postmarketing). Vaccine coverage increased to ≈32%–48% in France, Spain, and Belgium but remained <1% in England and Wales. Serotype 1 incidence rose in all age groups and countries (incidence rate ratio [IRR] 1.3–4.2; p<0.004), independently of PCV7 use, but incidence of serotypes 7F and 19A increased most in France, Spain, and Belgium (IRR 1.9–16.9 in children <5 years; p<0.001), where PCV7 coverage was greater. Vaccine-induced replacement of PCV7 serotypes possibly contributed to NVT increases, as did secular trends. New vaccines targeting these serotypes are available, but serotype dynamics needs further exploration that accounts for underreporting and prevaccine trends.